British Sociologists and French 'Sociologues' in the Interwar Years : the battle for society - Rocquin, Baudry (Switzerland : Palgrave Macmillan, 2019)
This book is a comparative study of the development of sociology in Britain and France between 1920 and 1940, taking a broad definition of the discipline to examine divergence across the channel in the interwar years. Rocquin charts the tension between differing schools of thought, presenting an alternative history of Europe based on cultural and intellectual struggle, and variation in theoretical visions of society - a divide that is still crucial in understanding the present situation between Continental Europe and the United Kingdom. This is a compelling addition to the history of sociology, and will be of interest to students and scholars across history, historical sociology, politics, European studies, and the sociology of knowledge.
Includes bibliographical references and index.
Description based on publisher-supplied MARC data.
Keywords: Historical sociology; Social history; Social sciences -- Philosophy